Business Intelligence Systems and Their Impact on Organizational Decision-Making and Performance Outcomes: Literature Review - Adek Wahyu Nugroho; Anak Agung Gde Satia Utama (Politeknik Ganesha Medan, 2025)
This study examines the role of Business Intelligence (BI) in decision-making and organizational performance. BI is an essential tool for collecting, analyzing, and presenting relevant data, thereby supporting management in making more accurate and data-driven decisions. The method used in this study is thematic synthesis, where relevant literature is gathered from various academic databases such as Google Scholar, ScienceDirect, and SCOPUS. Inclusion and exclusion criteria are applied to ensure that only high-quality and relevant studies are considered. The analysis results indicate that BI implementation can enhance operational efficiency and create a competitive advantage for organizations. However, the success of BI implementation heavily relies on management support, data quality, as well as technological readiness and human resource skills. This study also identifies the challenges faced in BI adoption, including data integration issues and the need for user training. The findings are expected to provide insights for organizations in leveraging BI to improve performance and make better decisions.